Rhythm and thought: the embodied trace of time in cognition - Carnero-Sierra, Susana (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This work aims to present a collection of apparently isolated data in their fields, which show how the rhythm constitutes a central organizing factor in the cognition of a wide range of species and in different vital functions. The exhibition of evidence will serve to consider this component of music as a key to the organization of the experience. The definition of rhythm, articulated beyond its aesthetic conception, will start from the perspective of embodied cognition, which supports the translation of the representation of the auditory rhythm towards its understanding as a form of embodied thinking, offering another point of dualistic overcoming of the study of the cognition abilities. The arguments will be organized in four areas: the theoretical framework of embodied cognition, the evolutionary study of infantile human development, the trace of rhythmic abilities in other species and the consolidation of rhythm interventions applied in different pathologies.
Keywords: rhythm; embodied cognition; forms of vitality; comparative psychology; music